Proximate and Phytochemical Analysis of Leaves of Anthocleista vogelii ( Cabbage palm) - Emem Ikpeme Bassey; Effiong Bassey Bassey; Ugbor Ofunna; Pheobe Ikechukwu (Kashmir Journal of Science)
The proximate and phytochemical analysis of leaves of Anthocleista vogelii was studied. The phytochemical screening indicated qualitatively the presence of alkaloids, saponins, flavonoids, polyphenols, tannins, reducing sugars, and the absence of phlobatanins, anthranoids. The results from the proximate composition indicate that the leaves contained some important nutrients such as Carbohydrate 52.50±0.60, Fatty acid 4.40±0.11, Fibre content 17.30±0.22 and Protein content 17.30±0.11. The presence of the phytoconstituents in Anthocleista vogelii shows that the plant contains essential nutrients, hence, it can be viewed as a potential component for the production of drugs